Characteristics and prognosis of patients with embolic stroke of undetermined source in China. Issue 5 (June 2022) - Yang, Xiaomeng; Jing, Jing; Meng, Xia; Li, Zixiao; Pan, Yuesong; Jiang, Yong; Xiang, Xianglong; Liu, Huan; Chen, Yu; Liu, Liping; Zhao, Xingquan; Wang, Yilong; et al.
Background and purpose: We aimed to explore the frequencies, risk factors, and natural history of embolic stroke of undetermined source (ESUS) through a national prospective registry in China. Methods: Between August 2015 and March 2018, the Third China National Stroke Registry recruited consecutive patients with ischemic stroke or transient ischemic attack in China. The baseline characteristics, risks of stroke, and prognosis in patients with embolic stroke of undetermined source were described and compared with that in patients with other causative subtypes. Results: A total of 15, 166 transient ischemic attack and ischemic stroke patients were enrolled in the Third China National Stroke Registry. Among 8528 ischemic stroke with standard diagnostic work-up, 2415 (28.3%) patients were diagnosed with embolic stroke of undetermined source. The mean age was 61 years and 70% of them were male. Compared to patients with cardioembolic strokes and small vessel disease, patients with embolic stroke of undetermined source had higher prevalence of nonstenosing large artery atherosclerosis (37.93% vs. 31.26%, P  = 0.008 and 37.93% vs. 34.40%, P  = 0.044 respectively). The cumulative probability of stroke recurrence in patients with embolic stroke of undetermined source at three months and one year was 5.59% and 8.74%. Compared with embolic stroke of undetermined source patients (0.70% and 1.99%), patients with the large artery atherosclerosis and cardioembolic strokes had higher cumulative probability of death at three months (1.94% and 3.22%) and one year (4.17% and 7.39%). Conclusions: Embolic stroke of undetermined source is a common cause of ischemic stroke in Chinese population with a higher stroke recurrence than previously reported. It was more likely to have nonstenosing large artery atherosclerosis in patients with embolic stroke of undetermined source than with cardioembolic strokes and small vessel disease.